Selection of lansoprazole from an FDA-approved drug library to inhibit the Alzheimer’s disease seed-dependent formation of tau aggregates - Imtiaz, Ahmed; Shimonaka, Shotaro; Uddin, Mohammad Nasir; Elahi, Montasir; Ishiguro, Koichi; Hasegawa, Masato; Hattori, Nobutaka; Motoi, Yumiko (Frontiers in Aging Neuroscience, 2024)
The efficacy of current treatments is still insufficient for Alzheimer’s disease (AD), the most common cause of Dementia. Out of the two pathological hallmarks of AD amyloid-β plaques and neurofibrillary tangles, comprising of tau protein, tau pathology strongly correlates with the symptoms of AD. Previously, screening for inhibitors of tau aggregation that target recombinant tau aggregates have been attempted. Since a recent cryo-EM analysis revealed distinct differences in the folding patterns of heparin-induced recombinant tau filaments and AD tau filaments, this study focused on AD seed-dependent tau aggregation in drug repositioning for AD. We screened 763 compounds from an FDA-approved drug library using an AD seed-induced tau aggregation in SH-SY5Y cell-based assay. In the first screening, 180 compounds were selected, 72 of which were excluded based on the results of lactate dehydrogenase assay. In the third screening with evaluations of soluble and insoluble tau, 38 compounds were selected. In the fourth screening with 3 different AD seeds, 4 compounds, lansoprazole, calcipotriene, desogestrel, and pentamidine isethionate, were selected. After AD seed-induced real-time quaking-induced conversion, lansoprazole was selected as the most suitable drug for repositioning. The intranasal administration of lansoprazole for 4 months to AD seed-injected mice improved locomotor activity and reduced both the amount of insoluble tau and the extent of phosphorylated tau-positive areas. Alanine replacement of the predicted binding site to an AD filament indicated the involvement of Q351, H362, and K369 in lansoprazole and C-shaped tau filaments. These results suggest the potential of lansoprazole as a candidate for drug repositioning to an inhibitor of tau aggregate formation in AD.